Primer design for extremely damaged DNA specimens of Asian rhinoceros species - Katanyuphan, Yada; Surat, Wunrada (Agriculture and Natural Resources, 2023)
Importance of the work: Small and highly damaged rhinoceros (rhino) specimens have been found; however, there are no primers for amplifying extremely damaged DNA remains of rhinos. Objectives: To design specific primers for tracking and identifying rhino species from extremely damaged DNA specimens. Materials & Methods: In total, 40 complete D-loop sequences of three Asian rhinos (Sumatran, Javan and Greater one-horned) were scanned for a region containing both intra- and inter-species variation. Phylogenetic trees were constructed and compared of the complete D-loop and selected fragments. Primer pairs covering the selected region were designed and tested for species specificity and sensitivity. Results: Most polymorphic sites selected were located between the 100–400 positions of the D-loop and the 257 bp fragment. The phylogenetic trees of the complete D-loop and the 257 bp sequences were constructed and compared to determine whether the region was a good representative of the complete D-loop. These trees showed similar topology, indicating that the 257 bp region was a good representative of the complete D-loop. For the future use of extremely damaged DNA specimens, three overlapping primer sets (Primers I, II and III) were designed covering the region. Phylogenetic trees were constructed of the DNA sequences within each primer set. The tree from the Primer II sequences had the greatest similarity to that of the complete D-loop. In addition, Primer II had high sensitivity, with a detection limit at 1 fg. Main finding: There were similar topologies between the phylogenetic tree of the complete D-loop and sequences within Primer II. Primer II could be used for rhino genetic studies of extremely damaged DNA specimens.